Perancangan Aplikasi Game Edukasi Pengenalan Komputer untuk Anak Didik Usia Sekolah Dasar - Azil Fahrurozie (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2019)
This event will be based on research by learning how important the Computer against the primary level, since with the introduction of computerized technology early on then the child will be familiar with computerized technology in the future.From all types of media, interactive entertainment media learning learning through games including one that has more value, because basically the game is for entertainment and with the Foundation of the learning media can make kids or students being more pleased in learning because they can play while learning at the same time.Making this game aims to add insight to children of the importance of technology, through this interactive game expected user or users feel interested and not feel bored in study.The research method used was the Software Development Life Cycle (SDLC) Water Fall and Game Design Document (GDD) who used the stage of the research (1) stage of analysis, (2) the stage of design, the programming phase (3), (4) the stage of testing, (5) stages maintenance.Needs analysis stage includes material and hardware and software requirements specifications.This form of the game is about questions concerning about the device and the computer functions with multiple choice answers.As well as answering the test, players stay clicking one answer to every question that appears by using the games with java applications.